STRATEGI GURU AL-QUR’AN HADITS DALAM MENGATASI KESULITAN BELAJAR MEMBACA AL-QUR’AN PESERTA DIDIK - Hepi Ikmal; Silvia Aprilia Setianingrum (Universitas Islam Lamongan, 2018)
This research aims to know the strategies of the Qur'an Hadith teacher in overcoming learning difficulties of students in reading the Qur'an; the supporting and inhibiting factors of the Qur'an Hadith teachers in overcoming learning difficulties of students in reading the Qur'an, and solutions to overcome the inhibiting factors in implementing the strategies of the Qur'an Hadith teachers to overcome the learning difficulties of students in reading the Qur'an. The results of research could be concluded as follows, first, the supporting and inhibiting factors in implementing the strategies of the Qur'an Hadith teachers in overcoming learning difficulties of students in reading the Qur'an that could be classified into two groups, namely: internal factors which include physiological factors such as illness, disability and talent, interest, and motivation. Types of learning difficulties faced by students in the subject of the Qur'an Hadith are not fluent in reading and writing the Qur'an, memorizing, interpreting, enriching and being capable of addressing the need of social reality. While the teacher's strategies in overcoming students' learning difficulties in the subject of the Qur'an Hadith through instruction, personal guidance, parental guidance and remedial teaching.